Does Work Stress Influence the Psychological Well-Being of Outsourcing Employees in Jabodetabek? - Edi Qurniyawan`; Adrian Wijanarko (LP2M IAIN Palopo, 2025)
This study investigates the influence of work stress on the psychological well-being of outsourced employees in the Jabodetabek region, Indonesia. The research background demonstrates that regulatory expansions permitting outsourcing in core business functions have intensified employment precarity and occupational stress among outsourced workers. This descriptive quantitative research examined 122 outsourced employees through validated questionnaires measuring work stress (19 items) and psychological well-being (26 items). Data were collected via online and face-to-face questionnaire administration, with simple linear regression analysis conducted using IBM SPSS Statistics version 25 software following classical assumption testing. The validity tests confirmed all 45 measurement items as valid (r-values ranging 0.581 to 0.934), while reliability testing achieved exceptional Cronbach's Alpha coefficients for work stress (0.963) and psychological well-being (0.985), both exceeding the 0.70 threshold. Results from simple linear regression analysis revealed that work stress exerts a statistically significant negative influence on psychological well-being (t-value = 11.396; p = 0.000; beta = 0.721). The regression equation Y = 152.316 + 1.265X demonstrates that each unit increase in work stress corresponds to a 1.265-point decrease in psychological well-being. The coefficient of determination (R² = 0.520) indicates that work stress accounts for 52% of the variation in psychological well-being outcomes. Findings confirm that work stress systematically and significantly diminishes psychological well-being among outsourced employees, necessitating comprehensive organizational interventions including stress management programs, flexible work arrangements, and enhanced occupational health support specifically designed for precarious workers.